Sustainable condition of the agricultural sector's environmental, economic, and social components from the perspective of open innovation - Alexander Semin; Oleg Betin; Lyudmila Namyatova; Elena Kireeva; Larisa Vatutina; Andrei Vorontcov; Nadezhda Bagaeva (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The aim of the study is to elaborate an econometric model to determine the conditionsfor ensuring the balanced development of environmental, economic, and social components of theRussian agricultural sector within the Eastern European region. The method of fuzzy sets was usedto build an integral model for assessing the level of sustainable development of the agricultural sectorin Eastern Europe on the basis of economic, environmental, and social sustainability indicators. Thecontrol indicators (independent variables) and integral economic, environmental, social sustainability(dependent variables) helped build multifactor linear regression models and calculate the indicatorsof elasticity of dependent variables from independent variables, which characterize the change insustainable development indicators with the growth of controlling factors by 1%. This model allowsus to define and analyze the levels of sustainable development of the industry, both in a specificcountry and within the region in general. The study shows that, for Russia and Eastern Europeancountries, innovation is one of the crucial factors in ensuring sustainable development of agriculturein the region, taking into account the current state and level of economic development.
Keywords: 650; agriculture; Eastern Europe; efficiency; innovation; Russia; sustainable development